Fluorescence Turn‐on of Tetraphenylethylene Derivative by Transfer from Cyclodextrin to Liposomes, HeLa Cells, and E. coli. Issue 10 (4th January 2023) - Masuda, Kosuke; Omokawa, Riku; Kawasaki, Riku; Mise, Yuta; Ooyama, Yousuke; Harada, Shogo; Shinoda, Wataru; Ikeda, Atsushi
Abstract: Herein, trimethyl‐β‐cyclodextrin (TMe‐β‐CDx) and γ‐cyclodextrin (γ‐CDx) could dissolve a tetraphenylethylene derivative (TPE−OH4 ) in water through high‐speed vibration milling. The fluorescence intensity of the TMe‐β‐CDx−TPE−OH4 complex was much higher than that of the γ‐CDx−TPE−OH4 complex, as the rotation of the central C=C double bond of TPE−OH4 after photoactivation was inhibited in a smaller TMe‐β‐CDx cavity in comparison with the γ‐CDx cavity. In contrast, the fluorescence intensity of the γ‐CDx−TPE−OH4 complex was very weak; nevertheless, it increased after the addition of liposomes due to the transfer of TPE−OH4 from the γ‐CDx cavity to the lipid membrane as a "turn‐on" phenomenon. Furthermore, to apply temperature sensor, it was demonstrated that the fluorescence intensity in the liposomes depended on the phase‐transition temperature. By using the fluorescence turn‐on phenomenon, TPE−OH4 could detect the presence of HeLa cells and E. coli by fluorescence. Abstract : It's fluorescence time ! Although the tetraphenylethylene derivative (TPE−OH4 ) was fluorescence OFF state in γ‐cyclodextrin (γ‐CDx), the fluorescence turn‐on was observed in the liposomes, HeLa cells, and E. coli, because TPE−OH4 was transferred from the γ‐CDx cavity to the lipid or cell membranes.